1995
DOI: 10.1074/jbc.270.21.12343
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the B-cell Surface Receptor CD40 Induces A20, a Novel Zinc Finger Protein That Inhibits Apoptosis

Abstract: CD40 activation is critical for B-cell function, leading to activation and expression of cell surface markers, proliferation, immunoglobulin class switching and inhibition of programmed cell death (PCD). Germinal center B-cells, for example, can be prevented from undergoing PCD by CD40 activation. The mechanism by which PCD is inhibited has been an enigma. A potential role for A20, a novel zinc finger protein, in inhibiting B-cell apoptosis was suggested by our previous finding that it is induced by the Epstei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
99
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(105 citation statements)
references
References 28 publications
4
99
2
Order By: Relevance
“…DRAK1, a positive mediator of apoptosis, is related to Death-associated Protein Kinase 1 (DAP1). 15 TXBP151 is a novel anti-apoptotic gene that has been shown to mediate the activity of A20, which is induced by CD40/CD40L interaction, 16,17 and its proteolysis is associated with FASmediated apoptosis. IL15 was also overexpressed in the BCL2 translocated cases and it has been implicated in protecting B cells from apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…DRAK1, a positive mediator of apoptosis, is related to Death-associated Protein Kinase 1 (DAP1). 15 TXBP151 is a novel anti-apoptotic gene that has been shown to mediate the activity of A20, which is induced by CD40/CD40L interaction, 16,17 and its proteolysis is associated with FASmediated apoptosis. IL15 was also overexpressed in the BCL2 translocated cases and it has been implicated in protecting B cells from apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, CD40 signaling has been reported to prevent apoptosis in lymphocytes and in some tumors, such as bladder carcinomas. 2,3,12 The antiapoptotic effect of CD40 stimulation is based on evidence of transcriptional upregulation of a number of negative regulators of cell death, such as Bcl-x L , Bfl1 and A20, 29,30 and activation of phosphatidylinositol 3-kinase-Akt, 31 which could counteract in tumor cells a proapoptotic effect of CD154. 28 These apparently conflicting results may depend on cell type-specific signaling.…”
Section: Discussionmentioning
confidence: 99%
“…CD40 ligation in B cells induces a number of phenotypic changes similar to those observed upon LMP1 expression, including upregulation of CD23 and CD54 and induction of homotypic cell adhesion. In addition, both LMP1 and CD40 signalling result in up-regulation of the expression of certain anti-apoptotic proteins, such as A20 and members of the bcl-2 family, which may at least partly account for the survival advantage confered by CD40 engagement or LMP1 expression in normal B-cells (Henderson et al, 1991;Laherty et al, 1992;Rowe et al, 1994;Choi et al, 1995;Sarma et al, 1995). Studies from our and other laboratories have shown that CD40 is not only expressed in lymphoid cells but it is also present in normal, basal epithelial cells and in a number of carcinomas including ovarian, nasopharyngeal, bladder and breast (Stamenkovic et al, 1989;Young et al, 1989;Banchereau et al, 1994;Gallagher et al, manuscript in preparation), where its role remains widely unknown.…”
Section: Introductionmentioning
confidence: 99%